LRRK2 Targeting Strategies as Potential Treatment of Parkinson’s Disease - Dominika Natalia Wojewska; Arjan Kortholt (Biomolecules, 2021)
Parkinson’s Disease (PD) affects millions of people worldwide with no cure to halt the progress of the disease. Leucine-rich repeat kinase 2 (LRRK2) is the most common genetic cause of PD and, as such, LRRK2 inhibitors are promising therapeutic agents. In the last decade, great progress in the LRRK2 field has been made. This review provides a comprehensive overview of the current state of the art, presenting recent developments and challenges in developing LRRK2 inhibitors, and discussing extensively the potential targeting strategies from the protein perspective. As currently there are three LRRK2-targeting agents in clinical trials, more developments are predicted in the upcoming years.